UiTM Sarawak pays courtesy visit to the Chief Minister of Sarawak - Chung, Ellen (UiTM Sarawak, 2021)
On 15th September 2020, Rector, Professor Dato Dr Jamil Haji Hamali, paid a courtesy visit to YB Datuk Haji Abdul Karim Rahman Hamzah, Minister ofTourism, Arts and Culture Sarawak at his office located at Bangunan Baitulmakmur (MASJA). Also present at the meeting were Dr Ellen Chung and Dr Robin Chang.